2015
DOI: 10.3389/fpsyg.2015.01365
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses are no substitute for registered replications: a skeptical perspective on religious priming

Abstract: According to a recent meta-analysis, religious priming has a positive effect on prosocial behavior (Shariff et al., 2015). We first argue that this meta-analysis suffers from a number of methodological shortcomings that limit the conclusions that can be drawn about the potential benefits of religious priming. Next we present a re-analysis of the religious priming data using two different meta-analytic techniques. A Precision-Effect Testing–Precision-Effect-Estimate with Standard Error (PET-PEESE) meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(147 citation statements)
references
References 27 publications
4
137
1
Order By: Relevance
“…This finding echoes more recent concerns, indicating that the observed relation between religiousness and prosociality may be restricted to self-report measures rather than actual behavioral measures (Galen, 2012;Shariff, 2015). Although it has been argued that experimental techniques such as religious priming might provide a solution to this problem (Willard, Shariff, & Norenzayan, 2016), methodological concerns (i.e., researcher and publication bias) severely limit the conclusions that can be drawn based on these studies (van Elk et al, 2015). Still, we note that the directionality of the effects that we reported is comparable to previous studies in which actual behavior (e.g., actual donations to religious charities) was measured (Bekkers & Schuyt, 2008;Bekkers & Wiepking, 2011b)-thereby increasing the confidence in the ecological validity of our measurements.…”
Section: Discussionsupporting
confidence: 52%
“…This finding echoes more recent concerns, indicating that the observed relation between religiousness and prosociality may be restricted to self-report measures rather than actual behavioral measures (Galen, 2012;Shariff, 2015). Although it has been argued that experimental techniques such as religious priming might provide a solution to this problem (Willard, Shariff, & Norenzayan, 2016), methodological concerns (i.e., researcher and publication bias) severely limit the conclusions that can be drawn based on these studies (van Elk et al, 2015). Still, we note that the directionality of the effects that we reported is comparable to previous studies in which actual behavior (e.g., actual donations to religious charities) was measured (Bekkers & Schuyt, 2008;Bekkers & Wiepking, 2011b)-thereby increasing the confidence in the ecological validity of our measurements.…”
Section: Discussionsupporting
confidence: 52%
“…Although the robustness analysis showed that this had little effect on the present results, it does illustrate very well the need for high-power N + 2 studies in the future. Although meta-analysis is a good tool for summarizing evidence, it is no substitute for replication studies (Van Elk et al, 2015). In this sense, we recommend that high-power, registered replications of N + 2 studies be undertaken in the future.…”
Section: Do N + 2 Preview Effects Exist?mentioning
confidence: 99%
“…van Elk et al (2015) point out that conclusions from meta-analyses are often limited, due to methodological shortcomings. Bias-correction techniques often can be inconsistent across a range of conditions, requiring ranges of effect size interpretations instead of the use of a single technique (Inzlicht et al, 2015).…”
Section: The Path Forwardmentioning
confidence: 99%